Analysis of Classroom Interaction Using IRF Pattern: A Case Study of EFL Conversation Class - Risna Saswati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
This study sheds lights on whether the use of Initiation, Response and Feedback (IRF) in teaching facilitates learner-initiated communication and gives learning opportunity for learners to engage in classroom interaction. This study applies the IRF framework proposed by Sinclair and Coulthard (1975), Initiation from (Mackey (2012) and teacher talk by CUllen (1988). The method applied for this study is qualitative method by classroom observation as the technique for data collection. The video records the classroom observation. The data are taken from classroom interaction of conversation class. The result of this study is the IRF pattern which mostly occurs in classroom interaction can be used to analyze classroom interaction. Additionally, the teaching using IRF pattern can facilitate learner-initiated communication and give learning opportunities for leaners to engage more in classroom interaction.Key words: IRF Pattern, learner-initiated communication, classroom interaction